Field-induced Optically Isotropic State in Bent Core Nematic Liquid Crystals: Unambiguous Proof of Field-induced Optical Biaxiality - Hegde, Gurumurthy; Elamain, Omaima; Fodor-Csorba, Katalin; Komitov, Lachezar (IOP Publishing, 2013)
The behaviour of bent core (BC) nematic liquid crystals was investigated under dc applied electric field. The optically isotropic state of a sample containing BC nematic was observed under application of low dc electric fields. The quality of the dark state when the sample was inserted between two crossed polarizers was found to be superb and it did not change when rotating the sample between the polarizers. The coupling between the net molecular dipole moment and the applied dc electric field was considered as the origin of the out-of-plane switching of the BC molecules resulting in switching from the field-off bright state to the field-on dark state. The field-induced optically isotropic state is an unambiguous proof of the field-induced biaxiality in the BC nematic liquid crystal. A simple model explaining the appearance of the isotropic optical state in BC nematics and the switching of the sample slow axis between three mutually orthogonal directions under dc applied electric field is proposed.